Perspectives of folate biofortification of cereal grains. (26th November 2018) - Wakeel, Abdul; Arif, Shazia; Bashir, Muhammad Asaad; Ahmad, Zeeshan; Rehman, Hafeez ur; Kiran, Aysha; Ibrahim, Saira; Khan, Muhammad Ramzan
Abstract: One sixth of the world's population is suffering from hidden hunger that indicates a gross malnutrition particularly among children and women of third world countries. The deficiency of micro nutrients, especially iron (Fe) causes a number of ailments such as megaloblastic anemia and neural tube defects in poor population. There is a dire need to supplement iron in the diet. Current efforts implicate fortification of wheat flour and other grains with different iron formulations such as ethylenediaminetetraacetic acid (EDTA), FeSO4 and elemental iron. However, all such interventions are not sustainable due to logistic and quality assurance problems in resource-limited settings. For a long term solution, development of crop plants with increased micronutrients and iron bioavailability is essential. Therefore, biofortification of cereal grains using translational genomics approaches for enhancement of folate through genome editing in cereals is inevitable to mitigate the folate deficiency in poor remote population in a cost effective manner.